2014
DOI: 10.1007/s00192-014-2468-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic syndrome and pelvic organ prolapse severity

Abstract: Introduction and hypothesisAs in the case of cardiovascular and metabolic diseases, the prevalence of pelvic organ prolapse (POP) has been rising with the increasing proportion of elderly women in the population. The purpose of the present cross-sectional study was to evaluate the components of metabolic syndrome (MS) in urogynecological patients with a variable POP severity.MethodsThe MS risk factors (elevated waist circumference, elevated triglycerides, decreased high-density lipoprotein cholesterol, elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
1
10
0
2
Order By: Relevance
“…Pelvic examination was performed with the patient in the dorsal lithotomy position. The POP-Q system was used to quantify the POP severity at a maximum Valsalva strain [12,15,16].…”
Section: Study Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic examination was performed with the patient in the dorsal lithotomy position. The POP-Q system was used to quantify the POP severity at a maximum Valsalva strain [12,15,16].…”
Section: Study Groupsmentioning
confidence: 99%
“…The patients with grade ≥1 or showing a positive cough stress test were considered to have SUI. The OAB symptoms were assessed using questions selected from the Pelvic Floor Distress Inventory [16,19] (BDo you usually experience frequent urination?B, BDo you usually experience a strong feeling of urgency to empty your bladder?^, BDo you usually experience urine leakage associated with a feeling of urgency, that is, a strong sensation of needing to go to the bathroom?^). The patients who answered Byes^to any of the questions were considered to have OAB [16].…”
Section: Study Groupsmentioning
confidence: 99%
“…В настоящее время опублико-ваны многочисленные работы по разработке новых методов лечения ВЖПО, постоянно совершенствуются методы хирургическо-го лечения. Практически во всех развитых странах мира разработаны клинические про-токолы диагностики и лечения ВЖПО [1][2][3][4][5][6]. В то же время есть трудности раннего начала лечебно-профилактических мероприятий [7].…”
Section: Msh Askerova Lm Rzakulieva Azerbaijan State Advanced Trunclassified
“…Установленный возрастной интервал для отбора единицы наблюдения обусловлен большей распространённостью ВЖПО по данным литературы в этих возрастных группах [1][2][3][4][5][6]. Наблюдение проведено про-спективно на базе женской консультации 7-го родильного дома в г. Баку.…”
Section: Msh Askerova Lm Rzakulieva Azerbaijan State Advanced Trunclassified
“…Epidemiological studies have revealed that the incidence of POP in women between 51 and 60 years old is 0.33%, whereas in women over 60 years old it is up to 0.71%. In addition, only 11% of POP patients undergo surgical treatment, and among them, 25% may relapse . POP manifests a number of clinical features.…”
Section: Introductionmentioning
confidence: 99%